Catholics offering prayer at the Basilica - Mumbai Archive Project Team (Jio Institute, 2024)
Bandra Catholics come to seek the intercession of the Blessed Virgin Mary during troubled times, praying for miracles and offering thanksgiving for the fulfilment of vows and wishes. The devotion to Mary, known as Marian's devotion, is a central aspect of Catholic spirituality.